Disaster Preparedness Education Program for Nursing Staff - Iwan Shalahuddin; Bambang Aditya Nugraha; Nurul Darmawulan; Shafira Rizki Amalia; Feni Agustina; Akmal Sybromillys; Ikhsan Hafidz (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Preparedness in the face of a disaster is one of the important elements of activities in reducing the risk and impact of a disaster, this is very much needed during a disaster, therefore a disaster education program is needed to prepare nurses' preparedness so that they can provide fast, accurate service and save victims from physical disability and death. The aim of the literature study is to identify a disaster education program to prepare the preparedness of nursing personnel in both institutional and acute settings. The method used is narrative review. Search for data using electronic data sources, such as PubMed, ScienceDirect, and Garuda Portal. The articles found will be selected based on the full paper with the publication year 2011-2021, open access, publications in English and Indonesian, while articles that are not relevant to the research topic and duplicated will be issued. Increasing disaster preparedness for nurses, namely by providing education coupled with special training, while nursing students by providing modules, peer group discussions, and evaluating materials included in the curriculum.Abstrak: Kesiapsiagaan dalam menghadapi suatu bencana merupakan salah satu elemen penting dari kegiatan dalam mengurangi risiko dan dampak bencana hal ini sangat dibutuhkan selama bencana, oleh karena itu program edukasi bencana dibutuhkan  guna mempersiapkan kesiapsiagaan perawat agar dapat memberikan pelayanan cepat akurat dan menyelamatkan korban dari cacat fisik dan kematian. Tujuan dari studi literatur untuk mengidentifikasi program edukasi bencana guna mempersiapkan kesiapsiagaan tenaga keperawatan baik dalam institusional maupun acute setting. Metode yang digunakan adalah narrative review. Pencarian data menggunakan sumber data elektronik, seperti PubMed, ScienceDirect, dan Portal Garuda. Artikel yang ditemukan akan diseleksi berdasarkan fullpaper dengan tahun publikasi 2011-2021, open access, publikasi dengan Bahasa Inggris maupun Bahasa Indonesia, sedangkan artikel yang tidak relevan dengan topik penelitian dan terduplikasi akan dikeluarkan. Peningkatan kesiapsiagaan bencana pada perawat yaitu dengan pemberian edukasi yang ditambah dengan pelatihan khusus, sementara mahasiswa keperawatan dengan pemberian modul, peer group discussion, dan evaluasi materi yang dimasukkan kedalam kurikulum.